4(y+5)-6(2y+3)=3(y+14)-2(5-y)+9

Simple and best practice solution for 4(y+5)-6(2y+3)=3(y+14)-2(5-y)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y+5)-6(2y+3)=3(y+14)-2(5-y)+9 equation:


Simplifying
4(y + 5) + -6(2y + 3) = 3(y + 14) + -2(5 + -1y) + 9

Reorder the terms:
4(5 + y) + -6(2y + 3) = 3(y + 14) + -2(5 + -1y) + 9
(5 * 4 + y * 4) + -6(2y + 3) = 3(y + 14) + -2(5 + -1y) + 9
(20 + 4y) + -6(2y + 3) = 3(y + 14) + -2(5 + -1y) + 9

Reorder the terms:
20 + 4y + -6(3 + 2y) = 3(y + 14) + -2(5 + -1y) + 9
20 + 4y + (3 * -6 + 2y * -6) = 3(y + 14) + -2(5 + -1y) + 9
20 + 4y + (-18 + -12y) = 3(y + 14) + -2(5 + -1y) + 9

Reorder the terms:
20 + -18 + 4y + -12y = 3(y + 14) + -2(5 + -1y) + 9

Combine like terms: 20 + -18 = 2
2 + 4y + -12y = 3(y + 14) + -2(5 + -1y) + 9

Combine like terms: 4y + -12y = -8y
2 + -8y = 3(y + 14) + -2(5 + -1y) + 9

Reorder the terms:
2 + -8y = 3(14 + y) + -2(5 + -1y) + 9
2 + -8y = (14 * 3 + y * 3) + -2(5 + -1y) + 9
2 + -8y = (42 + 3y) + -2(5 + -1y) + 9
2 + -8y = 42 + 3y + (5 * -2 + -1y * -2) + 9
2 + -8y = 42 + 3y + (-10 + 2y) + 9

Reorder the terms:
2 + -8y = 42 + -10 + 9 + 3y + 2y

Combine like terms: 42 + -10 = 32
2 + -8y = 32 + 9 + 3y + 2y

Combine like terms: 32 + 9 = 41
2 + -8y = 41 + 3y + 2y

Combine like terms: 3y + 2y = 5y
2 + -8y = 41 + 5y

Solving
2 + -8y = 41 + 5y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-5y' to each side of the equation.
2 + -8y + -5y = 41 + 5y + -5y

Combine like terms: -8y + -5y = -13y
2 + -13y = 41 + 5y + -5y

Combine like terms: 5y + -5y = 0
2 + -13y = 41 + 0
2 + -13y = 41

Add '-2' to each side of the equation.
2 + -2 + -13y = 41 + -2

Combine like terms: 2 + -2 = 0
0 + -13y = 41 + -2
-13y = 41 + -2

Combine like terms: 41 + -2 = 39
-13y = 39

Divide each side by '-13'.
y = -3

Simplifying
y = -3

See similar equations:

| -5=15-4y | | (a^2)(b^4)= | | 0.08x+0.06(300-x)=20 | | A-5=-1 | | 2w+2(2w-5)=26 | | 7x-1-4x=7 | | 6a+37=9-a | | 7y+8=-4+6y | | -6f=60-f | | 25-[10-(2-12)]+(5-343)= | | 6.4=.63x+4.51 | | -7+7x=-91 | | 14.35=-5.2 | | -3x+123=-12x-147 | | 55w+50(4.4-w)=233 | | 14x=8x | | K-6=4 | | 8x=14x | | -10=5(2x-4) | | x^2-6x-3=-6 | | 7n^2-6=106 | | f-(-.125)=.3 | | .7-a=.5 | | 3*8-4y=12 | | 38-4y=12 | | Y+0.5x=4 | | 6x=5x-12 | | 8b-4=-28 | | 390=60(t) | | 3(x+4)+2(x-1)=5 | | 7+k=12 | | (3x-5)=(2x+8) |

Equations solver categories